Perencanaan dan Perancangan Wisata Pantai Watu Bale Kebumen Dengan Pendekatan Konsep Arsitektur Vernakular - Miarsono, Harry; Dewi, Emmi Rostika; Murti, Mega Ayu (Jurnal Pelita Teknologi, 2020)
Planning and Designing Watu Bale Beach Tourism in Kebumen using the Vernacular Architecture Concept Approach aims to create a tourist destination that is in harmony with the natural environment and local culture. This study identifies the potential and challenges in developing Watu Bale Beach as a tourist destination, and explores how the principles of vernacular architecture can be used to achieve this goal. The vernacular architectural approach emphasizes the use of local materials, traditional building techniques, and design that adapts to the local climate and environmental conditions. By integrating elements of local culture and tradition, this project not only focuses on aesthetic aspects, but also environmental and economic sustainability. The results of this planning and design show that the application of vernacular architecture can increase tourist attraction, minimize negative effects on the environment, and empower local communities through active participation in the development and management of tourist destinations. This conclusion is expected to be a guide to the development of other beach tourism in the Kebumen area and its surroundings